2013
DOI: 10.1080/10810730.2013.768728
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Message Sensation Value and Psychological Reactance: A Test of the Dominant Thought Disruption Hypothesis

Abstract: The present study tests to see whether perceived message sensation value reduces psychological reactance within the context of anti-marijuana ads for television. After controlling for sensation seeking, biological sex, and marijuana use, the results indicate that message novelty is negatively associated with a freedom threat, whereas dramatic impact and emotional arousal were not associated with the antecedent to reactance. Results support the use of novel messages in future ads while at the same time offer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…These findings should be seen in the context of a broader set studies finding local participation in program selection and development linked to improvements in the implementation of prevention programs (Payne et al, 2006). The negative response of some educators is consistent with psychological reactance theory's prediction that prevention programs restricting choice may elicit emotional responses, negative cognitions, and efforts to reassert decision control (Quick, 2013).…”
Section: Implementation Factors Limiting the Impact Of Antibullying Psupporting
confidence: 66%
“…These findings should be seen in the context of a broader set studies finding local participation in program selection and development linked to improvements in the implementation of prevention programs (Payne et al, 2006). The negative response of some educators is consistent with psychological reactance theory's prediction that prevention programs restricting choice may elicit emotional responses, negative cognitions, and efforts to reassert decision control (Quick, 2013).…”
Section: Implementation Factors Limiting the Impact Of Antibullying Psupporting
confidence: 66%
“…There is some evidence that message sensation value (specifically, message novelty) is associated with freedom threat and reactance (Quick, 2013). Xu (2015) found that message sensation value interacts with controlling language such that high sensation value and high controlling messages arouse the greatest anger.…”
Section: Empathymentioning
confidence: 99%
“…Furthermore, high sensation messages are thought to be particularly appealing to high sensation seekers, as these messages meet their psychobiological needs for activation (Palmgreen et al, 2002;Stephenson, 2003). Quick (2013) found partial support for the role of perceived message sensation value as a message strategy for deterring reactance. In Quick's study (Quick et al, 2013), undergraduates were exposed to a series of anti-marijuana PSAs.…”
Section: Message Sensation Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the majority of persuasion theories, which predict when persuasive attempts will successfully elicit attitude or behavior change, PRT predicts when persuasive attempts are likely to be met with resistance or other unintended effects. For example, PRT has been identified as a viable explanation for the persuasiveness (or lack thereof) of television public service announcements (PSAs) on topics such as drunk driving, antismoking (Xu, 2015), condom use (Quick, 2013), and organ donation (Reinhart & Anker, 2012); college students' negative credibility appraisals of graphic warning labels on cigarette packages (LaVoie, Quick, Riles, & Lambert, 2015); and rates of underage alcohol consumption following changes in alcohol consumptions laws (Allen, Sprenkel, & Vitale, 1994).…”
Section: Theoretical Overview and Applicationsmentioning
confidence: 99%